Multi-metal carbon-based catalyst as well as preparation method and application thereof
The problems of high cost and poor stability of existing fuel cell catalysts are solved by using polymetallic carbon-based catalysts prepared by sugars, various metal compounds and nitrogen-containing compounds, and an environmentally friendly and efficient catalyst alternative is provided.
Patent Information
- Application Number
- CN202411335889.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-07
AI Technical Summary
Existing fuel cell catalysts mainly rely on precious metal platinum carbon, which is costly and poorly stable, making it difficult to meet environmentally friendly and sustainable development needs.
A multimetallic carbon-based catalyst prepared from sugars, various metal compounds and nitrogen-containing compounds is used to form a bimetallic carbon-based catalyst with excellent redox properties through anitrogenation and pH neutralization treatment.
It provides a low-cost, environmentally friendly catalyst with good stability and excellent catalytic activity at high current density, and can replace commercial platinum carbon catalysts.
Smart Images

Figure CN119275301A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of redox catalysts, and in particular to a multi-metal carbon-based catalyst and a preparation method and application thereof. Background Art
[0002] Fossil energy (including coal, oil and natural gas) has long been the main source of energy. However, the overuse of fossil fuels has led to an energy crisis and many environmental and climate problems, such as greenhouse gas emissions and global warming. In order to cope with these problems and achieve sustainable energy development, people have begun to look for new energy technologies. Fuel cells are considered to be a sustainable energy technology with great potential, and their main advantages include high efficiency conversion, zero emissions, low noise and flexibility. They can be widely used in transportation, power supply, construction and mobile equipment. Moreover, fuel cells can use various renewable energy sources, such as solar energy, wind energy and biomass energy, to produce hydrogen. Redox reaction is the core step of fuel cell energy conversion. However, the mainstream catalysts on the market are mainly platinum-carbon-based precious metal catalysts, which are expensive and have poor stability. Therefore, it is urgent to find a catalyst that is environmentally friendly, low-cost and has good stability and catalytic activity.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a multi-metal carbon-based catalyst and a preparation method and application thereof.
[0005] Specifically, the technical solution of the present invention is as follows: In the first aspect, the present invention provides a multi-metal carbon-based catalyst, which is prepared from raw materials including sugars, metal compounds, nitrogen-containing compounds and pore-forming agents; the weight proportion of the sugars is 0.15~0.25; there are at least two metal compounds, and the weight proportion of each metal compound is 0.16~0.47; the weight proportion of the nitrogen-containing compound is 2.5~5.
[0006] Preferably, the metal compound is selected from at least two of a copper-containing compound, an iron-containing compound and a cobalt-containing compound.
[0007] Preferably, the metal compound is selected from chlorides, acetates and sulfates.
[0008] Preferably, the metal compound is selected from ferric acetate and cobalt acetate; or, the metal compound is selected from ferric chloride and cupric chloride.
[0009] Preferably, the weight portion of ferric acetate is 0.15-0.23; and / or, the weight portion of cobalt acetate is 0.12-0.20; and / or, the weight portion of ferric chloride is 0.20-030; and / or, the weight portion of cupric chloride is 0.42-0.52.
[0010] Preferably, the pore-forming agent is sodium chloride.
[0011] Preferably, the nitrogen-containing compound is selected from urea and / or dicyandiamide.
[0012] Preferably, the weight ratio of sugars to nitrogen-containing compounds is 1:(12-26.6).
[0013] In a second aspect, the present invention provides a method for preparing the multi-metal carbon-based catalyst, which is based on sugars and undergoes nitrogen hybridization and pH neutralization treatment; The nitrogen hybridization treatment includes: heating the sugar, metal compound and nitrogen-containing compound to 800±50°C at a heating rate of 5±1°C / min at room temperature (about 20±5°C) and keeping the temperature for 1±0.2h.
[0014] The pH neutralization treatment comprises: placing the material after the nitrogen hybridization treatment in water to obtain a suspension, adjusting the pH value of the suspension to 1-1.5, stirring at 200-700 r / min for 5±2h; adjusting the pH value of the suspension to neutral, and drying.
[0015] The present invention uses bimetallic doping to chemically modify sugar carbon, and then performs nitrogen doping to obtain a bimetallic carbon-based catalyst. The bimetallic carbon-based catalyst provided by the present invention has safe and environmentally friendly raw materials, and has excellent redox properties, and can be widely used in various fuel cells and metal-air batteries, providing a new idea for replacing expensive commercial platinum carbon.
[0016] In a third aspect, the present invention provides the use of the multi-metal carbon-based catalyst or the preparation method in the production of fuel cells or metal-air batteries.
[0017] Beneficial effects: The present invention provides a multi-metal carbon-based catalyst and a preparation method and application thereof. The multi-metal carbon-based catalyst of the present invention is prepared from raw materials including sugars, metal compounds, nitrogen-containing compounds and pore-forming agents; the weight portion of sugars is 0.15-0.25; there are at least two metal compounds, each of which has a weight portion of 0.16-0.47; and the weight portion of nitrogen-containing compounds is 2.5-5. The multi-metal carbon-based catalyst provided by the present invention has good stability and excellent catalytic activity at high current density. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be described below.
[0019] Figure 1 Linear voltammetric scans of multi-metal carbon-based catalysts prepared in different embodiments and comparative examples provided by the present invention.
[0020] Figure 2 The cyclic voltammetry curves of the multi-metal carbon-based catalysts prepared in different embodiments and comparative examples provided by the present invention are shown.
[0021] Figure 3 It is a comparison chart of the hydrogen peroxide generation rate and the electron transfer number of the multi-metal carbon-based catalyst and platinum carbon prepared in Example 6 and Comparative Example 5 provided by the present invention.
[0022] Figure 4 It is a Tafel plot comparing the multi-metal carbon-based catalyst prepared in Example 6 provided by the present invention with platinum carbon.
[0023] Figure 5 CV graphs and linear voltammetric scanning graphs of Example 6 (left figure) and platinum carbon (right figure) provided by the present invention at the beginning and after 2000 cycles. DETAILED DESCRIPTION
[0024] Sugar is a renewable resource and is more environmentally friendly than traditional catalysts. The material cost of using it as a raw material to prepare multi-metal carbon-based catalysts (such as bimetallic carbon-based catalysts) is low, and after proper treatment, it has a rich porous structure and a large specific surface area, which can provide more catalytic sites, thereby showing good catalytic activity. However, compared with metal phase catalysts, bimetallic carbon-based materials have poor conductivity, which may limit their catalytic activity in high current density reactions. In addition, problems such as decarbonization or structural changes may occur during long-term use, thereby affecting its long-term stability. In order to solve the corresponding technical problems, the present invention modifies sugar carbon-based materials by adding metal hydroxides and nitrogen-containing compounds to prepare a multi-metal carbon-based catalyst with good stability and excellent catalytic activity at high current density.
[0025] In a more preferred and specific embodiment: Firstly, the present invention provides a bimetallic carbon-based catalyst, which is prepared from raw materials including the following components: sugars, two metal compounds and nitrogen-containing compounds.
[0026] Furthermore, in parts by weight, the sugar is 0.15 to 0.25 parts, each metal compound is 0.16 to 0.47 parts, and the nitrogen-containing compound is 2.5 to 5 parts.
[0027] Furthermore, the mass ratio of the sugar to the nitrogen-containing compound is 1:(12-26.6).
[0028] Furthermore, the raw materials also include acid and water.
[0029] Furthermore, the metal compound is selected from at least two of cupric chloride, ferric chloride, ferric acetate and cobalt acetate.
[0030] Furthermore, the nitrogen-containing compound is selected from one or both of dicyandiamide and urea.
[0031] Secondly, the present invention also provides a method for preparing the above-mentioned bimetallic carbon-based catalyst, which is based on sugars and undergoes nitrogen hybridization treatment and pH neutralization.
[0032] The present invention adds nitrogen-containing compounds during the nitrogen hybridization process.
[0033] Furthermore, the nitrogen hybridization treatment includes: heating the sugar, the metal compound, and the nitrogen-containing compound to 800° C. at a temperature of 5° C. / min for 1 h to obtain a crude sample; The present invention adopts a continuously increasing temperature method during the nitrogen hybridization process of sugars, and the obtained bimetallic carbon material has a better specific surface area and catalytic performance.
[0034] Furthermore, the pH neutralization includes: placing the crude carbon sample prepared by the nitrogen hybridization treatment in water to obtain a suspension; adding an acid to adjust the pH value of the suspension to acidic and stirring for 5 hours to obtain an acidic suspension; washing the acidic suspension with water to neutrality, then filtering and drying to obtain a product.
[0035] Furthermore, the pH value is preferably adjusted to 1-1.5.
[0036] Furthermore, the acid used may be an acidic solution commonly used in the art, such as a hydrochloric acid solution, and the amount used may be 1 / (50-1000) of the volume of the suspension.
[0037] Furthermore, the rotation speed of the stirring process is 200~700r / min.
[0038] The present invention uses acid to treat the crude sample and then performs neutralization treatment to make it neutral, which can effectively improve the catalytic performance of the sugar carbon material.
[0039] Furthermore, the mass ratio of the sugar to the nitrogen-containing compound is 1:(12-26.6).
[0040] Again, the present invention provides a bimetallic carbon-based catalyst prepared by the preparation method.
[0041] In addition, the present invention also provides the use of the carbon-based catalyst or the bimetallic carbon-based catalyst in fuel cells and metal-air batteries.
[0042] The present invention provides a bimetallic carbon-based catalyst based on sugars and a corresponding preparation method thereof. The present invention uses bimetallic doping to chemically modify sugar carbon, and then performs nitrogen doping to obtain a bimetallic carbon-based material with good stability and excellent catalytic activity at high current density, which can meet the catalyst performance requirements of current fuel cells. The bimetallic carbon-based catalyst provided by the present invention is environmentally friendly and low in cost. It can meet the requirements of sustainable development while ensuring economic benefits, and provides a new idea for the research and development of alternatives to the currently expensive commercial platinum carbon.
[0043] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] The endpoints and any values of the ranges disclosed in this specification are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0045] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "specific implementations", or "some specific implementations" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0046] In the examples provided in this specification, if no specific techniques or conditions are specified, the techniques or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.
[0047] Example 1
[0048] This embodiment provides a carbohydrate-based multimetallic carbon-based catalyst, and the specific preparation method is as follows: Take 0.19 g of ferric acetate, 0.16 g of cobalt acetate, 1 g of NaCl, 0.15 g of sucrose, and 4 g of urea in a tubular furnace, set the heating rate to 5 °C / min, raise the temperature in the tube to 800 °C and calcine for 1 h, and finally cool naturally to room temperature to obtain a crude sample for stand-by use.
[0049] Take the crude sample in a 50mL beaker, add 50mL of deionized water, add 1mol / L dilute hydrochloric acid solution to adjust the solution to acidity and stir at a stirring rate of 500r / min for 5h to obtain an acidic solution of a certain concentration.
[0050] The acidic solution is added with an appropriate amount of deionized water to wash the solution to neutrality. After obtaining the neutral solution, it is filtered and the wet carbon is placed in an oven to dry to obtain the product.
[0051] The prepared multi-metal carbon-based catalyst was subjected to linear voltammetry and cyclic voltammetry tests using a rotating disk electrode apparatus. The half-wave potential and starting potential were used to reflect the catalytic activity of the catalyst. The results are shown in Figure 1 and Figure 2 As shown, the half-wave potential and starting potential of the multi-metal carbon-based catalyst prepared in this embodiment are 0.8040V and 0.89758V.
[0052] Example 2
[0053] This embodiment provides a carbohydrate-based multimetallic carbon-based catalyst, and the specific preparation method is as follows: Take 0.19 g of ferric acetate, 0.16 g of cobalt acetate, 1 g of NaCl, 0.15 g of sucrose, and 3 g of urea in a tubular furnace, set the heating rate to 5 °C / min, raise the temperature in the tube to 800 °C and calcine for 1 h, and finally cool naturally to room temperature to obtain a crude sample for stand-by use.
[0054] Take the crude sample in a 50mL beaker, add 50mL of deionized water, add 1mol / L dilute hydrochloric acid solution to adjust the solution to acidity and stir at a stirring rate of 500r / min for 5h to obtain an acidic solution of a certain concentration.
[0055] The acidic solution is added with an appropriate amount of deionized water to wash the solution to neutrality. After obtaining the neutral solution, it is filtered and the wet carbon is placed in an oven to dry to obtain the product.
[0056] The prepared multi-metal carbon-based catalyst was subjected to linear voltammetry and cyclic voltammetry tests using a rotating disk electrode apparatus. The half-wave potential and starting potential were used to reflect the catalytic activity of the catalyst. The results are shown in Figure 1 and Figure 2As shown, the half-wave potential and starting potential of the multi-metal carbon-based catalyst prepared in this embodiment are 0.8670V and 0.9050V.
[0057] Example 3
[0058] This embodiment provides a carbohydrate-based multimetallic carbon-based catalyst, and the specific preparation method is as follows: Take 0.19 g of ferric acetate, 0.16 g of cobalt acetate, 1 g of NaCl, 0.15 g of sucrose, and 3.5 g of urea in a tubular furnace, set the heating rate to 5 °C / min, raise the temperature in the tube to 800 °C and calcine for 1 h, and finally cool naturally to room temperature to obtain a crude sample for stand-by use.
[0059] Take the crude sample in a 50mL beaker, add 50mL of deionized water, add 1mol / L dilute hydrochloric acid solution to adjust the solution to acidity and stir at a stirring rate of 500r / min for 5h to obtain an acidic solution of a certain concentration.
[0060] The acidic solution is added with an appropriate amount of deionized water to wash the solution to neutrality. After obtaining the neutral solution, it is filtered and the wet carbon is placed in an oven to dry to obtain the product.
[0061] The prepared multi-metal carbon-based catalyst was subjected to linear voltammetry and cyclic voltammetry tests using a rotating disk electrode apparatus. The half-wave potential and starting potential were used to reflect the catalytic activity of the catalyst. The results are shown in Figure 1 and Figure 2 As shown, the half-wave potential and starting potential of the multi-metal carbon-based catalyst prepared in this embodiment are 0.8490V and 0.8980V.
[0062] Example 4
[0063] Take 0.25 g of ferric chloride, 0.47 g of copper chloride, 0.25 g of NaCl, and 0.25 g of maltose, add deionized water to prepare a solution, stir for 8 hours, and then perform freeze-drying pretreatment.
[0064] Add 5 g of dicyandiamide to the pretreated product, put it into a tubular furnace, set the heating rate to 5°C / min, raise the temperature inside the tube to 800°C and calcine for 1 hour, and finally cool it naturally to room temperature to obtain a crude sample for standby use.
[0065] Take the crude sample in a 50mL beaker, add 50mL of deionized water, add 1mol / L dilute hydrochloric acid solution to adjust the solution to acidity and stir at a stirring rate of 500r / min for 6h to obtain an acidic solution of a certain concentration.
[0066] The acidic solution is added with an appropriate amount of deionized water to wash the solution to neutrality. After obtaining the neutral solution, it is filtered and the wet carbon is placed in an oven to dry to obtain the product.
[0067] The prepared multi-metal carbon-based catalyst was subjected to linear voltammetry and cyclic voltammetry tests using a rotating disk electrode apparatus. The half-wave potential and starting potential were used to reflect the catalytic activity of the catalyst. The results are shown in Figure 1 and Figure 2 As shown, the half-wave potential and starting potential of the multi-metal carbon-based catalyst prepared in this embodiment are 0.7890V and 0.8318V.
[0068] Example 5
[0069] Take 0.25 g of ferric chloride, 0.47 g of copper chloride, 2 g of NaCl, and 0.25 g of maltose, add deionized water to prepare a solution, stir for 8 hours, and then perform freeze-drying pretreatment.
[0070] Add 5 g of dicyandiamide to the pretreated product, put it into a tubular furnace, set the heating rate to 5°C / min, raise the temperature inside the tube to 800°C and calcine for 1 hour, and finally cool it naturally to room temperature to obtain a crude sample for standby use.
[0071] Take the crude sample in a 50mL beaker, add 50mL of deionized water, add 1mol / L dilute hydrochloric acid solution to adjust the solution to acidity and stir at a stirring rate of 500r / min for 6h to obtain an acidic solution of a certain concentration.
[0072] The acidic solution is added with an appropriate amount of deionized water to wash the solution to neutrality. After obtaining the neutral solution, it is filtered and the wet carbon is placed in an oven to dry to obtain the product.
[0073] The prepared multi-metal carbon-based catalyst was subjected to linear voltammetry and cyclic voltammetry tests using a rotating disk electrode apparatus. The half-wave potential and starting potential were used to reflect the catalytic activity of the catalyst. The results are shown in Figure 1 and Figure 2 As shown, the half-wave potential and starting potential of the multi-metal carbon-based catalyst prepared in this embodiment are 0.8430V and 0.8567V.
[0074] Example 6
[0075] Take 0.25 g of ferric chloride, 0.47 g of copper chloride, 1.5 g of NaCl, and 0.25 g of maltose, add deionized water to prepare a solution, stir for 8 hours, and then perform freeze-drying pretreatment.
[0076] Add 2.5 g of dicyandiamide to the pretreated product, put it into a tubular furnace, set the heating rate to 5°C / min, raise the temperature inside the tube to 800°C and calcine for 1 hour, and finally cool it naturally to room temperature to obtain a crude sample for standby use.
[0077] Take the crude sample in a 50mL beaker, add 50mL of deionized water, add 1mol / L dilute hydrochloric acid solution to adjust the solution to acidity and stir at a stirring rate of 500r / min for 6h to obtain an acidic solution of a certain concentration.
[0078] The acidic solution is added with an appropriate amount of deionized water to wash the solution to neutrality. After obtaining the neutral solution, it is filtered and the wet carbon is placed in an oven to dry to obtain the product.
[0079] The prepared multi-metal carbon-based catalyst was subjected to linear voltammetry and cyclic voltammetry tests using a rotating disk electrode apparatus. The half-wave potential and starting potential were used to reflect the catalytic activity of the catalyst. The results are shown in Figure 1 and Figure 2 As shown, the half-wave potential and starting potential of the multi-metal carbon-based catalyst prepared in this example are 0.8670V and 0.9065V, and it still has good catalytic activity after two thousand scans. The electron transfer number-hydrogen peroxide conversion rate and Tafel curve are plotted, where the hydrogen peroxide conversion rate is 1.36%, and the corresponding Tafel curve slope is as high as 137mV / dec. The data results show that Figure 3 , Figure 4 .
[0080] Example 7
[0081] Take 0.25 g of ferric chloride, 0.47 g of copper chloride, 1.5 g of NaCl, and 0.25 g of maltose, add deionized water to prepare a solution, stir for 8 hours, and then perform freeze-drying pretreatment.
[0082] Add 3 g of dicyandiamide to the pretreated product, put it into a tubular furnace, set the heating rate to 5°C / min, raise the temperature inside the tube to 800°C and calcine for 1 hour, and finally cool it naturally to room temperature to obtain a crude sample for standby use.
[0083] Take the crude sample in a 50mL beaker, add 50mL of deionized water, add 1mol / L dilute hydrochloric acid solution to adjust the solution to acidity and stir at a stirring rate of 500r / min for 6h to obtain an acidic solution of a certain concentration.
[0084] The acidic solution is added with an appropriate amount of deionized water to wash the solution to neutrality. After obtaining the neutral solution, it is filtered and the wet carbon is placed in an oven to dry to obtain the product.
[0085] The prepared multi-metal carbon-based catalyst was subjected to linear voltammetry and cyclic voltammetry tests using a rotating disk electrode apparatus. The half-wave potential and starting potential were used to reflect the catalytic activity of the catalyst. The results are shown in Figure 1 and Figure 2 As shown, the half-wave potential and starting potential of the multi-metal carbon-based catalyst prepared in this embodiment are 0.7580V and 0.8407V.
[0086] Comparative Example 1
[0087] This comparative example provides a multi-metal carbon-based catalyst based on sugars, and the specific preparation method is as follows: Take 0.19 g of ferric acetate, 0.16 g of cobalt acetate, 0.15 g of sucrose, and 4 g of urea in a tubular furnace, set the heating rate to 5°C / min, raise the temperature in the tube to 800°C and calcine for 1 hour, and finally cool naturally to room temperature to obtain a crude sample for stand-by use.
[0088] Take the crude sample in a 50mL beaker, add 50mL of deionized water, add 1mol / L dilute hydrochloric acid solution to adjust the solution to acidity and stir at a stirring rate of 500r / min for 5h to obtain an acidic solution of a certain concentration.
[0089] The acidic solution is added with an appropriate amount of deionized water to wash the solution to neutrality. After obtaining the neutral solution, it is filtered and the wet carbon is placed in an oven to dry to obtain the product.
[0090] The prepared multi-metal carbon-based catalyst was subjected to a linear voltammetric scan test using a rotating disk electrode device to reflect the catalytic activity of the catalyst with its half-wave potential. Figure 1 As shown, the half-wave potential of the multi-metal carbon-based catalyst prepared in Comparative Example 1 is 0.7960V. The hydrogen peroxide conversion rate is 15.43%. The data results show that Figure 3 .
[0091] Comparative Example 2
[0092] This comparative example provides a carbohydrate-based multimetallic carbon-based catalyst, and the specific preparation method is as follows: Take 0.16g of cobalt acetate, 1g of NaCl, 0.15g of sucrose, and 3g of urea in a tubular furnace, set the heating rate to 5°C / min, raise the temperature in the tube to 800°C and calcine for 1h, and finally cool naturally to room temperature to obtain a crude sample for stand-by use.
[0093] Take the crude sample in a 50mL beaker, add 50mL of deionized water, add 1mol / L dilute hydrochloric acid solution to adjust the solution to acidity and stir at a stirring rate of 500r / min for 5h to obtain an acidic solution of a certain concentration.
[0094] The acidic solution is added with an appropriate amount of deionized water to wash the solution to neutrality. After obtaining the neutral solution, it is filtered and the wet carbon is placed in an oven to dry to obtain the product.
[0095] The prepared multi-metal carbon-based catalyst was subjected to a linear voltammetric scan test using a rotating disk electrode device to reflect the catalytic activity of the catalyst with its half-wave potential. Figure 1As shown, the half-wave potential of the catalyst prepared in Comparative Example 2 is 0.7150V.
[0096] Comparative Example 3
[0097] This comparative example provides a multi-metal carbon-based catalyst based on sugars, and the specific preparation method is as follows: Take 0.19 g of ferric acetate, 0.16 g of cobalt acetate, 1 g of NaCl, and 0.15 g of sucrose in a tube furnace, set the heating rate to 5°C / min, raise the temperature in the tube to 800°C and calcine for 1 hour, and finally cool naturally to room temperature to obtain a crude sample for stand-by use.
[0098] Take the crude sample in a 50mL beaker, add 50mL of deionized water, add 1mol / L dilute hydrochloric acid solution to adjust the solution to acidity and stir at a stirring rate of 500r / min for 5h to obtain an acidic solution of a certain concentration.
[0099] The acidic solution is added with an appropriate amount of deionized water to wash the solution to neutrality. After obtaining the neutral solution, it is filtered and the wet carbon is placed in an oven to dry to obtain the product.
[0100] The prepared multi-metal carbon-based catalyst was subjected to a linear voltammetric scan test using a rotating disk electrode device to reflect the catalytic activity of the catalyst with its half-wave potential. Figure 1 As shown, the half-wave potential of the multi-metal carbon-based catalyst prepared in Comparative Example 3 is 0.5900V.
[0101] Comparative Example 4
[0102] Take 0.47 g of copper chloride, 1.5 g of NaCl, and 0.25 g of maltose, add deionized water to prepare a solution, stir for 8 hours, and then perform freeze-drying pretreatment.
[0103] Add 2.5 g of dicyandiamide to the pretreated product, put it into a tubular furnace, set the heating rate to 5°C / min, raise the temperature inside the tube to 800°C and calcine for 1 hour, and finally cool it naturally to room temperature to obtain a crude sample for standby use.
[0104] Take the crude sample in a 50mL beaker, add 50mL of deionized water, add 1mol / L dilute hydrochloric acid solution to adjust the solution to acidity and stir at a stirring rate of 500r / min for 6h to obtain an acidic solution of a certain concentration.
[0105] The acidic solution is added with an appropriate amount of deionized water to wash the solution to neutrality. After obtaining the neutral solution, it is filtered and the wet carbon is placed in an oven to dry to obtain the product.
[0106] The prepared multi-metal carbon-based catalyst was subjected to linear voltammetry and cyclic voltammetry tests using a rotating disk electrode apparatus. The half-wave potential and starting potential were used to reflect the catalytic activity of the catalyst. The results are shown in Figure 1 and Figure 2 As shown, the half-wave potential of the multi-metal carbon-based catalyst prepared in Comparative Example 4 is 0.3370V.
[0107] Comparative Example 5
[0108] Take 0.25 g of ferric chloride, 0.47 g of copper chloride, 1.5 g of NaCl, and 0.25 g of maltose, add deionized water to prepare a solution, stir for 8 hours, and then perform freeze-drying pretreatment.
[0109] The pretreated product was placed in a tubular furnace, the heating rate was set to 5°C / min, the temperature inside the tube was raised to 800°C and calcined for 1 hour, and finally naturally cooled to room temperature to obtain a crude sample for standby use.
[0110] Take the crude sample in a 50mL beaker, add 50mL of deionized water, add 1mol / L dilute hydrochloric acid solution to adjust the solution to acidity and stir at a stirring rate of 500r / min for 6h to obtain an acidic solution of a certain concentration.
[0111] The acidic solution is added with an appropriate amount of deionized water to wash the solution to neutrality. After obtaining the neutral solution, it is filtered and the wet carbon is placed in an oven to dry to obtain the product.
[0112] The prepared multi-metal carbon-based catalyst was subjected to linear voltammetry and cyclic voltammetry tests using a rotating disk electrode apparatus. The half-wave potential and starting potential were used to reflect the catalytic activity of the catalyst. The results are shown in Figure 1 and Figure 2 As shown, the half-wave potential and starting potential of the multi-metal carbon-based catalyst prepared in Comparative Example 5 are 0.6320V and 0.8318V.
[0113] Comparative Example 6
[0114] Take 1.5g NaCl and 0.25g maltose, add deionized water to prepare a solution, stir for 8 hours, and then perform freeze-drying pretreatment.
[0115] Add 2.5 g of dicyandiamide to the pretreated product, put it into a tubular furnace, set the heating rate to 5°C / min, raise the temperature inside the tube to 800°C and calcine for 1 hour, and finally cool it naturally to room temperature to obtain a crude sample for standby use.
[0116] Take the crude sample in a 50mL beaker, add 50mL of deionized water, add 1mol / L dilute hydrochloric acid solution to adjust the solution to acidity and stir at a stirring rate of 500r / min for 6h to obtain an acidic solution of a certain concentration.
[0117] The acidic solution is added with an appropriate amount of deionized water to wash the solution to neutrality. After obtaining the neutral solution, it is filtered and the wet carbon is placed in an oven to dry to obtain the product.
[0118] The prepared multi-metal carbon-based catalyst was subjected to linear voltammetry and cyclic voltammetry tests using a rotating disk electrode apparatus. The half-wave potential and starting potential were used to reflect the catalytic activity of the catalyst. The results are shown in Figure 1 and Figure 2 As shown, the half-wave potential and starting potential of the multi-metal carbon-based catalyst prepared in Comparative Example 6 are 0.461V and 0.6825V.
[0119] The test results of the above Examples 1-7 and Comparative Examples 1-6 show that the catalytic yield can be significantly improved by adding sugars, inorganic metal compounds, and nitrogen-containing compounds in appropriate proportions in the solution provided by the embodiments of the present invention, among which the effect obtained by the ratio of Example 6 is particularly significant and is the best ratio.
[0120] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A multi-metal carbon-based catalyst, characterized in that: The invention is prepared from raw materials including sugar, metal compound, nitrogen-containing compound and pore-forming agent; the weight proportion of sugar is 0.15-0.25; there are at least two metal compounds, each of which is 0.16-0.47; and the weight proportion of nitrogen-containing compound is 2.5-5.
2. The multi-metal carbon-based catalyst according to claim 1, characterized in that: The metal compound is selected from at least two of a copper-containing compound, an iron-containing compound and a cobalt-containing compound.
3. The multi-metal carbon-based catalyst according to claim 1 or 2, characterized in that: The metal compound is selected from chlorides, acetates and sulfates.
4. The multi-metal carbon-based catalyst according to any one of claims 1 to 3, characterized in that: The metal compound is selected from ferric acetate and cobalt acetate; or, the metal compound is selected from ferric chloride and cupric chloride.
5. The multi-metal carbon-based catalyst according to claim 4, characterized in that: The weight portion of ferric acetate is 0.15-0.23; and / or, the weight portion of cobalt acetate is 0.12-0.20; and / or, the weight portion of ferric chloride is 0.20-030; and / or, the weight portion of cupric chloride is 0.42-0.
52.
6. The multi-metal carbon-based catalyst according to any one of claims 1 to 5, characterized in that: The pore-forming agent is sodium chloride.
7. The multi-metal carbon-based catalyst according to any one of claims 1 to 6, characterized in that: The nitrogen-containing compound is selected from urea and / or dicyandiamide.
8. The multi-metal carbon-based catalyst according to any one of claims 1 to 7, characterized in that: The weight ratio of sugars to nitrogen-containing compounds is 1:(12~26.6).
9. The method for preparing the multi-metal carbon-based catalyst according to any one of claims 1 to 8, characterized in that: Based on sugars, nitrogen hybridization and pH neutralization treatment are carried out; The nitrogen hybridization treatment comprises: heating the sugar, the metal compound, and the nitrogen-containing compound to 800±50°C at a heating rate of 5±1°C / min, and keeping the temperature for 1±0.2h; The pH neutralization treatment comprises: placing the material after the nitrogen hybridization treatment in water to obtain a suspension, adjusting the pH value of the suspension to 1-1.5, stirring at 200-700 r / min for 5±2h; adjusting the pH value of the suspension to neutral, and drying.
10. Use of the multimetallic carbon-based catalyst according to any one of claims 1 to 8 or the preparation method according to claim 9 in the production of fuel cells or metal-air batteries.